Neurocysticercosis Without Risk Factors - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
Two unusual cases of cysticercosis in children, ages 6 and 3 years, without risk factors or infected contacts, and five additional cases in children <2 years, are reported from Loyola University Chicago Stritch School of Medicine, Maywood, IL; University of Illinois at Chicago Medical Center; Children's Memorial Hospital, Chicago; and Centers for Disease Control and Prevention, Atlanta, GA.